Factors influencing the knowledge and practice of emergency contraception among Nigerian male undergraduates (2020)
Background: Unwanted pregnancies among young women is a growing reproductive health concern. Correct and consistent use of contraception will stop this ugly trend while emergency contraception (EC) can also be viewed as a 'second chance method' in preventing unwanted pregnancies and unsafe abortions. The aim of this study is to assess the knowledge and practice of emergency contraception among Nigerian male undergraduates as they are known to have risky sexual behaviours. Methodology: This was a cross sectional study involving three hundred and thirty male undergraduates from three Tertiary institutions in Ibadan. A Multi-staged random sampling technique was used to recruit participants. Results: Knowledge about EC was poor among majority (74.5%) of male undergraduates. About 55.2% of the participants were sexually active and out of which 33.9% are currently using EC. The commonly (67.5%) used EC by their partners was levonorgestrel only pill (Postinor). Participants with higher levels of education, awareness of EC, previous use or having a partner who had previously used EC, participants who had sex within the past 6 months and those who were willing to recommend EC to others had a better knowledge of EC, which were all statistically significant. Conclusion: Providing accurate information to improve knowledge of EC among young men could lead to an increase in the uptake of EC.